¿Por qué las cópulas son auxiliares? - Gómez Rubio, Joshua (Borealis – An International Journal of Hispanic Linguistics, 2019)
Abstract. Copulas work as auxiliary verbs in Spanish and in other languages. In this article, we will argue in favor of this property being due to the absence of lexical content of the copula verb be1 (Sp. ‘ser’), on the one hand, and the aspectual content of the verb be2 (Sp. ‘estar’), on the other hand.